EMERGENCE OF ADVANCED DIGITAL TECHNOLOGY TO INCREASE PRODUCTIVITY IN CIVIL AND INFRASTRUCTURE INDUSTRY IN MALAYSIA - Ramaneswaran Subramaniam; Chandra Reka Ramachandiran (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Advanced Digital Technology is an automated instrument and resource that collects, stores, or processes data from every organisation’s current infrastructure. Advanced Digital Technology uses in Malaysia are growing every day as part of the policies of the ruling government and the Malaysian construction industry is projected to experience a Compound Annual Growth Rate of 4.7% over the prediction period from 2019 to 2024. The construction was funded by the 10th Malaysian Initiative, in which the Government spent heavily in highways, industrial parks, and residential buildings. Within the transportation and development sector, there are range of categories, spanning from homebuilders to businesses who sponsor large government-funded programs. Forecasted that embracing the Advanced Digital Technologies by numbers of major Civil and Infrastructure Industry in Malaysia will increase the productivity. Through a technical standpoint, the Civil and Infrastructure business are continuously innovating. By factual, there is productivity stagnant in Malaysian Civil and Infrastructure Industry. Organisations must combine proper adoption methods, which is why it may be one of the fastest sectors to implement modern adoption and to up the current productivity stagnant.Many of the leading players in the civil and infrastructure building industry in Malaysia, backed by an excellent track record of executing large-scale projects on schedule and powered by creative technological technologies that reshape the building market and the decision to integrate Advanced Digital Technology into their